EU charter of fundamental rights - Egeliği, Ömer Emrullah (My University, 2013)
Birlik, Avrupa kıtası için ekonomik bütünleşmeye dayanan bir barış projesidir. Ancak siyasal bütünleşme olmaksızın, Birlik amaçlarına ulaşılması mümkün değildir. Siyasal bütünleşme devletlerin birleşmesi kadar halkların da birleşmesini gerektirir. Halkların birleşmesi demokratik ve politik meşruiyetin sağlanması ile mümkündür. Birliğin politik meşruiyetini sağlaması için Birlik vatandaşlarının aidiyet duygusunun arttırılması gerekmektedir. Bu anlamda Birliğin insan hakları politikalarını geliştirmesi, anayasal milliyetçilik kavramı ile bağlantılı olarak Birlik vatandaşlarının aidiyet duygusunu arttıracaktır. Birlik makamları ilk dönemlerde insan hakları odaklı bir politika yürütmemiştir. Birlik yargı organı olan Avrupa Adalet Divanı da insan hakları yargılamasını, ilk dönem içtihatlarında sadece ekonomik bütünleşme odaklı, gerçekleştirmiştir. Ancak bu durum, zaman içerisinde Birlik hukukunun üstünlüğü gibi temel ilkelerin meşruiyeti sorgulanmasına neden olmuştur. Üye ülke anayasa mahkemelerinin insan hakları odaklı reaksiyonları, Birliğin insan hakları politikalarının öneminin farkına varmasını sağlamıştır. Birliğin demokratik organı olan Avrupa Parlamentosu siyasal girişimlerle, Avrupa Adalet Divanı da içtihatlarıyla Birlik içerisinde insan hakları politikalarını gündeme taşımıştır. Zamanla Birlik hukukunda korunan hakların daha açık, şeffaf ve öngörülebilir olması ihtiyacı ortaya çıkmıştır. Birlik hukukunda, bir temel haklar katalogu ihtiyacı sonunda “Avrupa Birliği Temel Haklar Şartı” kodifiye edilmiştir. Şart’ın hukuki statüsü Lizbon antlaşması ile birlikte Kurucu Antlaşmalarla aynı düzeye taşınmıştır. Şart ile Birlik tasarruflarında esas alınması gereken bir insan hakları belgesi meydana getirilmiştir. Tez, Şart’ı AB insan hakları hukukundaki tarihsel ve anayasal boyutları ile ele almaktadır. Şart’ın, Birlik insan hakları politikası evriminin genel seyrindeki konumu üzerine eğilmiştir. Ayrıca Şart’ın Birlik içerisindeki ve Birlik ile üye devletler arasındaki anayasal ilişkilere etkisini analiz edilmiştir. Şart ile Birlik insan hakları hukuku adına işlevsel ve etkin bir gelişmenin gerçekleşip gerçekleşmediği irdelenmiştir. Avrupa Birliği, İnsan Hakları, Avrupa Birliği Temel Haklar Şartı.

EU CHARTER OF FUNDAMENTAL RIGHTS The Union is a peace project based on the economic integration of the Europe. This Union could achieve its goals only through the maintenance of political integration. Political integration requires the integration of states and integration of peoples as well. Integration of peoples is only possible through the achievement of democratic and political legitimacy. Union citizens should be provided with the proper conditions to feel the sense of belonging to the Union in order to achieve political legitimacy. Therefore, the development of human rights by the Union would help increase the sense of belonging for the Union citizens in relation to the constitutional nationalism. The institutions of the Union did not pursue a human rights-focused policy in its early period. The European Court of Justice made judgments related to the human rights only within the framework of the economic purposes in the early period of its establishment. The legitimacy of the fundamental rights such as the supremacy of the Union law was begun to be questioned in the course of time. Human rights-related reactions of the constitutional courts of the member states helped the Union to realize the importance of the human rights policies. The European Parliament, as the democratic body of the Union, brought the human rights policies to the agenda through its political initiatives, and the European Court of Justice did the same through its judgments. The need for more clear, transparent and foreseeable rights protected under the Union law emerged in the course of time. Therefore, a fundamental rights catalogue was codified in the Charter of Fundamental Rights of the EU.The legal status of the Charter was made equal with the status of the Treaties under the Lisbon Treaty. Thus, a human rights document to be taken as a basis for the measures of the Union was drawn up. This thesis discusses the Charter considering its place in the historical and constitutional developments in the EU human rights law. It focuses on the position of the Charter in the general progress of the human rights policy. In addition, the Charter’s influence on the relations within the Union and between the Union and member states was analyzed. It was examined whether the Charter resulted in a functional and effective development in favor of the human rights law or not. Key words: European Union, Human Rights, the Charter of the Fundamental Rights of the European Union.
Keywords: Avrupa Birliği; Hukuk; İnsan Hakları